Pediatric Aspects of Malaria - V.A. Kirilenko; T.V. Kirilenko (Zaslavsky O.Yu., 2013)
The lecture focuses on the increasing danger of the spread of malaria in Ukraine. The paper summarizes recent data on the epidemiology, diagnosis, treatment and prevention of malaria in children.